2017
DOI: 10.1590/1413-81232017225.16722015
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade de medicamentos fitoterápicos e plantas medicinais nas unidades de atenção básica do Estado de São Paulo: resultados do Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica (PMAQ)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
(18 reference statements)
1
8
0
17
Order By: Relevance
“…75 Regarding the availability of phytotherapeutics and herbal medicines in the UBS's of the state of São Paulo -Brazil, only 11% had the availability of phytotherapeutics and or herbal medicines, corresponding to 16.1% of São Paulo cities. 76 Oliveira et al 77 78 These data correlates with the study carried out by doctors in the municipality of Canoas (Rio Grande do Sul, Brazil), who reported on the use of chamomile (33.3%) and Gingko biloba (18.5%). 73 Costa et al 79 reported that the use of phytotherapeutics is one of the main therapeutic options used by the population of the city of Campinas (São Paulo -Brazil), which can be explained by the implementation of the Municipal Phytotherapy Policy, which encourages the use and offers access to phytotherapeutics in municipal pharmacies.…”
Section: Medicinal Plants and Professionals Of Healthsupporting
confidence: 52%
See 1 more Smart Citation
“…75 Regarding the availability of phytotherapeutics and herbal medicines in the UBS's of the state of São Paulo -Brazil, only 11% had the availability of phytotherapeutics and or herbal medicines, corresponding to 16.1% of São Paulo cities. 76 Oliveira et al 77 78 These data correlates with the study carried out by doctors in the municipality of Canoas (Rio Grande do Sul, Brazil), who reported on the use of chamomile (33.3%) and Gingko biloba (18.5%). 73 Costa et al 79 reported that the use of phytotherapeutics is one of the main therapeutic options used by the population of the city of Campinas (São Paulo -Brazil), which can be explained by the implementation of the Municipal Phytotherapy Policy, which encourages the use and offers access to phytotherapeutics in municipal pharmacies.…”
Section: Medicinal Plants and Professionals Of Healthsupporting
confidence: 52%
“…An important factor that certainly contributes to the use of herbal medicines and phytotherapeutics in the municipalities are the municipal laws that guarantee in some way so the programs can remain independent of changes in political management and investments in the training of health professionals. 76…”
Section: Medicinal Plants and Professionals Of Healthmentioning
confidence: 99%
“…O conjunto dos trabalhos publicados mostra que, apesar da importância do PMAQ-AB para a sociedade, muitas contribuições são dadas no sentido de melhorar a Atenção Básica da saúde e o próprio PMAQ-AB. Alguns trabalhos apresentam análises com relação aos insumos das Unidades Básicas de Saúde, como Caccia et al (2017) que, particularizando para o Estado de São Paulo, estuda a disponibilidade de medicamentos fitoterápicos e plantas medicinais nas unidades de atenção básica de saúde.…”
Section: Trabalhos Relacionadosunclassified
“…A utilização empírica nos leva a crer que o poder anti-inflamatório das plantas ainda é pouco estudado, contudo, o potencial tóxico de uma planta não pode ser negligenciado. O uso indevido das plantas pode acarretar a danos graves, tanto locais como sistêmicos (CACCIA-BAVA et al, 2017, HASENCLEVER et al, 2017.…”
Section: Introducãounclassified